2019
DOI: 10.1088/1742-6596/1218/1/012025
|View full text |Cite
|
Sign up to set email alerts
|

Metacognitive activity of male students: difference field independent-dependent cognitive style

Abstract: The study aimed to explore the metacognitive activities of male students who were independent field cognitive style and field dependent cognitive style in solving problems. The type of this research is explorative with qualitative approach, that is from written works and in-depth interviews. Data analysis is done through data reduction, data presentation, data interpretation and conclusion drawing. The results showed that male students with field independent cognitive style, had a tendency to be structured, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 6 publications
2
5
0
Order By: Relevance
“…This is in accordance with research of Yang that male are better than female in constructing and using theories [22]. Likewise, the results of the study by Pathuddin et al [23] that male students with independent cognitive styles, tendencies to have structured and well-organized knowledge in proposing problem solving and can rearrange new information and relate it to the knowledge they have. This is in accordance with the opinion of Casey [24], and Maccoby & Jacklyn [25] that groups of boys rely on spatial strategies when completing mental rotation tasks, while groups of girls tend to use verbal strategies to accomplish this task.…”
Section: Discussionsupporting
confidence: 89%
“…This is in accordance with research of Yang that male are better than female in constructing and using theories [22]. Likewise, the results of the study by Pathuddin et al [23] that male students with independent cognitive styles, tendencies to have structured and well-organized knowledge in proposing problem solving and can rearrange new information and relate it to the knowledge they have. This is in accordance with the opinion of Casey [24], and Maccoby & Jacklyn [25] that groups of boys rely on spatial strategies when completing mental rotation tasks, while groups of girls tend to use verbal strategies to accomplish this task.…”
Section: Discussionsupporting
confidence: 89%
“…Future studies are suggested to explore the differences between genders (Pathuddin et al, 2019) and their impact on the quality of the use of problem-solving strategies and the achievement in problem-solving. The six factors identified by EFA will interpret the dimension of students' understanding of metacognition when they are solving physics problems.…”
Section: Suggestionsmentioning
confidence: 99%
“…Also, the development of PMI is based on the MAI pattern which consists of 6 (six) dimensions and focuses on the use of diagrams in solving physics problems (Taasoobshirazi & Farley, 2013). Most research examines metacognition in solving physical problems using oral interviews by developing several items (Balta et al, 2016;Kryjevskaia et al, 2014;Mansyur, Lestari, Werdhiana, & Rizal, 2018;Mundilarto, 2003;Pathuddin, Budayasa, & Lukito, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Compared to girls with the FI classification, boys with that classification performed significantly better. Moreover, Pathuddin et al (2019) specifically studied the characteristics of male students with different cognitive styles in solving mathematics problems. Boys with the FI cognitive style were typically capable of reshaping and connecting new information to the knowledge they already possessed and organised in resolving problems.…”
Section: Cognitive Styles and Gendermentioning
confidence: 99%